Geometry-Driven Field-Induced Single-Ion Magnetism in Hexagonal Bipyramidal Tb3+ and Ho3+ Complexes - Aravena-Ponce, D; Aravena-Ponce, D (American Chemical Society, 2025)
The synthesis of the precursors [Ln(LN6en)(CH3COO)2](BPh4)<middle dot>nH2O (Ln = Tb, n = 0, 1; Ln = Ho, n = 1, 2<middle dot>H2O), followed by a ligand exchange reaction with triphenylsilanolate, results in the isolation of the complexes {[Ln(LN6en)(OSiPh3)2](BPh4)}<middle dot>2CH2Cl2 (Ln = Tb, 3<middle dot>2CH2Cl2; Ln = Ho, 4<middle dot>2CH2Cl2). Single-crystal X-ray diffraction studies of 3<middle dot>2CH2Cl2 and 4<middle dot>2CH2Cl2 revealed that both compounds adopt a hexagonal bipyramidal geometry. Magnetic characterization shows that the complexes behave as single-ion magnets (SIMs) under an optimal applied field of 2000 Oe. Notable, these are the first reported Tb3+ and Ho3+ complexes with a hexagonal bipyramidal coordination geometry to exhibit such magnet-like behavior. Furthermore, they constitute the first field-induced Tb3+ and Ho3+ SIMs incorporating a macrocyclic ligand in a nonsandwich topology. Magnetic measurements indicate that the applied field only partially suppresses quantum tunneling of magnetization (QTM) and that at higher temperatures magnetic relaxation is dominated by the Raman process rather than the Orbach mechanism. These experimental observations are supported by ab initio calculations, which provide detailed insights into the electronic structure, including the splitting of f-orbital energy levels, thereby elucidating the origin of the observed magnetic behavior in both cases.